2021
DOI: 10.1088/1755-1315/782/3/032022
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany of the Arecaceae family in Torgamba District, South Labuhanbatu, North Sumatra

Abstract: Ethnobotany is a branch of science that studies the relationship between humans and plants. The arecaceae family is found in Indonesia and is widely used by people throughout the region Study ethnobotany of the Arecaceae family in South Labuhanbatu Regency, North Sumatra aims to make an inventory of the types of arecaceae species commonly used by the community. The types of arecaceae species found in South Labuhanbatu include coconut (Cocos nucifera), Aren (Arenga pinnata), Palm Oil (Elais guineensis), Areca n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In addition, Nuryanti et al (2015) stated that the Cocos nucifera that comes from the Arecaceae are used to wrap the traditional dish named "ketupat" as the leaf is easy to be woven. Besides that, Rambey et al (2021) reported that the wide leaves of the Arecaceae are suitable to be used as food wrappers. Rini et al (2017) mentioned that Arecaceae have strong leaf fiber, which makes them difficult to tear and can make food last longer.…”
Section: Diversity Of Plant-based Food Wrappermentioning
confidence: 99%
“…In addition, Nuryanti et al (2015) stated that the Cocos nucifera that comes from the Arecaceae are used to wrap the traditional dish named "ketupat" as the leaf is easy to be woven. Besides that, Rambey et al (2021) reported that the wide leaves of the Arecaceae are suitable to be used as food wrappers. Rini et al (2017) mentioned that Arecaceae have strong leaf fiber, which makes them difficult to tear and can make food last longer.…”
Section: Diversity Of Plant-based Food Wrappermentioning
confidence: 99%